The access rate to diagnosis and treatment modalities in breast cancer patients in Turkey; Multicenter observational study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2011)
Purpose: To determine the time elapsed between the first notification of the disease and the access to the diagnosis and treatment modalities and the associated factors in female patients with breast cancer in Turkey. Methods: Data was acquired from a questionnaire involving 535 patients who applied to 14 various oncology clinics in Turkey between 1st and 28th of February 2010. Analyses were performed by the participating clinics and were divided into 3 groups: centers located in metropolitan areas formed group I (n=161), those located in Marmara and central Anatolia region formed group 2 (n=189), and centers located in Karadeniz and East-Southeast Anatolia region formed group 3 (n=185). The groups of these centers were formed according to the socioeconomic development of the provinces. Results: The median patient age was 48 years, 56.1% of patients were less than 50 years of age. Eighty-five percent of the patients detected a mass in their breast by self examination and 27% of the patients older than 50 years never had breast imaging until the definite diagnosis was established. The median time elapsed between disease noticed by the patient and application to a health care center was 10 days, between application and biopsy 19 days, between biopsy and surgery 10 days, and between surgery and systemic therapy 31 days. The median time elapsed between patients applying for surgery in groups I and 2 centers was 11 and 21 days, respectively (p=0.01). The median time elapsed between biopsy and surgery in groups 1,2 and 3 centers was 14,1.5, and 12 days, respectively (p<0.05). Conclusion: A high level of awareness regarding breast cancer in our country is related with the time that is defined as 10 days between disease recognition and medical application. The time elapsed between the application and biopsy, surgery and systemic therapy was longer compared with the corresponding figures in developed countries.
Keywords: breast cancer; elapsed time to diagnosis and treatment; socioeconomic factors; 1ST ADJUVANT THERAPY; WAITING TIME; CHEMOTHERAPY; SURVIVAL; DELAY